Mangrove Vegetation Community Structure in Sungai Sembilan Sub-District, Dumai City - Hasyim, Ardhan Fadhlani; Mulyadi, Aras; Efriyeldi, Efriyeldi (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2022)
Mangroves are one of the important ecosystems in coastal areas that grow in places that are still influenced by tides. This research was conducted from October to November 2019 in the mangrove ecosystem of Sungai Sembilan District, Dumai City, Riau Province. The purpose of this study was to determine the structure of mangrove vegetation in Sungai Sembilan District, Dumai City. The method used in this study was a survey method, and used 4 stations. The mangrove species obtained were Avicennia alba, Avicennia mariana, Rhizophora apiculata, R. mucronata, Sonneratia alba, Xylocarpus granatum and Nypa fruticans. The density of mangrove vegetation at stations I, II, and III has criteria 1000 to < 1500 Trees/Ha, while at station IV the criteria are damaged with tree density criteria < 1000 Trees/Ha. From the aspect of the index, the mangrove community has a diversity value (H') which is classified as moderate with sufficient productivity which has a value ranging from 1.70 to 2.36, the value of uniformity (E) is classified as uneven, which is around 0.25 to 0.34 and the index value is dominance (C) which is relatively low, ranging from 0.12 to 0.33 which means that there is no dominant species in the area. Based on the significance value, the vegetation type R. apiculata dominated by having a greater significance value than the other species as a whole at each station in the tree, sapling and seedling categories